Konsep Doa: Studi Komparasi Konsep Doa Menurut M. Quraish Shihab dan Yunan Nasution serta Relevansinya dengan Tujuan Pendidikan Islam. - Kurnia Muhajarah (Jurnal Hikmatuna, 2016)
Prayer holds significant meaning in life, encompassing not only the spiritual aspect but also the physical-biological and psychological aspects. Hence, prayer establishes a profound connection with the goals of Islamic education, which aim to develop not only the physical-biological aspects but also the spiritual aspect. This discourse employs qualitative research methodology, utilizing primary data from M. Quraish Shihab's book titled "Insight Qur'an about Remembrance and Prayer" and Yunan Nasution's "Living Handbook Volume 3." Additionally, secondary data from various relevant references on the theme are utilized. The discussion results reveal the strengths and weaknesses of both prayer concepts. The strength of M. Quraish Shihab's concept lies in its philosophical depth. However, it lacks practical examples from everyday life. On the other hand, Yunan Nasution's concept is easily understandable, but it tends to employ more colloquial language. In terms of the objectives of Islamic education, both concepts aim to achieve the following: (1) Enhancing individuals' potential to benefit themselves and the community, (2) Nurturing souls with noble qualities (al-karimah), and (3) Cultivating intelligent individuals with strong faith and taqwa (piety).